Adaptive threshold algorithm for detecting EEG-interburst intervals in extremely preterm neonates - Mader, Johannes; Hartmann, Manfred; Dressler, Anastasia; Oberdorfer, Lisa; Rona, Zsofia; Glatter, Sarah; Czaba-Hnizdo, Christine; Herta, Johannes; Kluge, Tilmann; Werther, Tobias; Berger, Angelika; Koren, Johannes; et al. (Physiological measurement, 2024)
Objective . This study provides an adaptive threshold algorithm for burst detection in electroencephalograms (EEG) of preterm infantes and evaluates its performance using clinical real-world EEG data. Approach . We developed an adaptive threshold algorithm for burst detection in EEG recordings from preterm infants. To assess its applicability in the real-world, we tested the algorithm on a dataset of 30 clinical EEG recordings which were not preselected for good quality, to ensure a real-world scenario. Main results . Interrater agreement was substantial at a kappa of 0.73 (0.68–0.79 inter-quantile range). The performance of the algorithm showed a similar agreement with one clinical expert of 0.73 (0.67–0.76) and a sensitivity and specificity of 0.90 (0.82–0.94) and 0.95 (0.93–0.97), respectively. Significance . The adaptive threshold algorithm demonstrated robust performance in detecting burst patterns in clinical EEG data from preterm infants, highlighting its practical utility. The fine-tuned algorithm achieved similar performance to human raters. The algorithm proves to be a valuable tool for automated burst detection in the EEG of preterm infants.